No bones about it - Krulik, Nancy E.; John & Wendy (New York : Grosset & Dunlap, 2004)
Katie and her third-grade class go on a field trip to the natural history museum where Katie finds herself magically transported into the body of their tour guide.
Keywords: School field trips -- Fiction; Natural history museums -- Fiction; Magic -- Fiction